Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 5887 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Morinda L.", "HasGeospatialIssue is false", "HasCoordinate is true", { "or" : [ "BasisOfRecord is Human Observation", "BasisOfRecord is Machine Observation", "BasisOfRecord is Observation", "BasisOfRecord is Material sample", "BasisOfRecord is Living Specimen", "BasisOfRecord is Literature Occurrence", "BasisOfRecord is Unknown evidence", "BasisOfRecord is Specimen" ] } ] } The dataset includes 5887 records from 154 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0073909-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences